Discovering the Self-Recovery Value in Justice Album by Justin Bieber - Nazira Riza; Salwa Nurhaliza; Euis Meinawati (Universitas Islam Negeri Palopo, 2025)
This study aims to investigate how Justin Bieber’s Justice album portrays self-recovery through the lens of Geoffrey Leech’s Seven Types of Meaning. Using a descriptive qualitative approach, five tracks (Lonely, Ghost, Off My Face, Hold On, and Anyone) were analyzed through content analysis to uncover patterns of meaning within the lyrics. The results indicate that Lonely and Ghost present themes of isolation, grief, and acknowledgement of internal conflict, representing the early stages of recovery. Off My Face and Hold Reveal emotional intensity, reliance, hope, and perseverance as the speaker navigates the process of regaining balance. In contrast, anyone reflects the desire for stability and meaningful connection. Overall, the analysis shows that Bieber’s use of language constructs a unified narrative of healing, aligning with self-recovery as a gradual reconstruction of emotional well-being and personal identity.